Hydroxychloroquine-induced hyperpigmentation in a patient with anti-synthetase syndrome - Claúdia Brazão; Raquel Campanilho-Marques; Pedro de Vasconcelos; Luís Soares-de-Almeida; Paulo Filipe (Revista da Sociedade Portuguesa de Dermatologia e Venereologia)
Hydroxychloroquine is a widely prescribed antimalarial drug to treat immune-mediated diseases, with a good safety profile. We present the case of a 37-year-old woman, Fitzpatrick’s phototype IV, who presented to our outpatient Dermatology Department with a 1-year history of symmetrical blue-gray discoloration on the anterior aspect of the legs. The patient had a diagnosis of anti-synthetase syndrome, treated with prednisolone, hydroxychloroquine, rituximab, cyclosporine, and acetylsalicylic acid. The blood work was unremarkable. The skin biopsy revealed hemosiderin and melanin (Perl’s and Fontana-Masson staining) deposits inside dermal histocytes. The diagnosis of antimalarial-induced hyperpigmentation was established. Cutaneous blue-gray discoloration is a common antimalarial skin toxicity, mainly in women with darker skin. Its pathophysiology is unclear, but local trauma, ultraviolet radiation, and the concomitant use of corticosteroids, anticoagulants, and antiplatelet drugs seem to contribute as triggers. This case illustrates that a high level of suspicion and adequate clinicopathologic correlation is necessary to establish a correct diagnosis.